EFEKTIVITAS KONTEN TIKTOK @AKUSRAPROSHOP.SMG SEBAGAI MEDIA PROMOSI AKUSARA BILLIARD PROSHOP SEMARANG - Lia Novita Anggraeni; Ratih Kurnia Putri; Dwi Rosmalasari; Siswandaru Kurniawan (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effectiveness of Akusara Billiard Proshop Semarang's TikTok promotional content in measuring consumer engagement, purchase intention, and loyalty. Social Media Marketing theory serves as a reference in this study. Quantitative research methods were applied using secondary data from TikTok Shop consumers and Akusara Proshop Semarang followers to test the influence of TikTok promotional content on the studied variables. The results of the study on H1 regarding the influence of customer engagement on Akusara's TikTok account promotional content showed a significant effect. Furthermore, H2 regarding the influence of purchase interest on Akusara's TikTok account promotional content showed a significant effect. For H3, the influence of consumer loyalty on Akusara's TikTok account promotional content showed a significant effect. And, H4 regarding the influence of customer engagement, purchase interest, and consumer loyalty on Akusara's TikTok account promotional content showed a significant effect.